ASSESSMENT OF IMMUNOLOGICAL DISORDERS IN THE GENESIS OF BRONCHIAL ASTHMA IN CHILDREN WITH DIFFERENT DEGREES OF THE DISEASES CONTROLLABILITY - Lytvynets, L.Ya.; Lytvynets-Golutyak, U.Ye.; Chopyak, V.V. (World of Medicine and Biology, 2018)
The study involved 87 children aged 6 to 18 years, patients with BA who were hospitalized in Ivano-Frankivsk Regional Pediatric Hospital at Allergic department during 2009-2010. The diagnosis of asthma was verified in accordance with the Protocol of diagnosis and treatment of BA in children № 868 from 03.10.2013. According to the level of controllability for asthma, taking into account the results of BA control test (GINA, 2009) the children were divided into two groups: 28 patients – with partially controlled asthma (PCBA), 22 patients – with uncontrolled asthma (UCBA) and 22 patients – with controlled asthma (CBA). The control group consisted of 10 children who live in different parts of Ivano-Frankivsk region, selected by random sampling.We studied cellular and humoral immunity using methods of direct rosette developing with erythrocytes coated with monoclonal antibodies to CD3 +, CD4 +, CD8 +, CD22 + (Production of Vitebsk Medical University, Belarus), CD4/CD8 values of immunoregulatory index and phagocytic immunity. State of nonspecific resistance was studied by determining the phagocytic activity of neutrophils (PA) and oxygen dependent metabolism in spontaneous NBT-test, functional reserve in terms of phagocytic cell numbers (PCN), an index of neutrophil activation in stimulated NBT test, made by the quantitative spectrophotometric method for T. Gentle i R. Thompson ("Renal", Hungary). The concentration of cytokines (IL-6 and IL-4) in serum were determined by ELISA in the machine "STAT-Fax 303 Plus" (USA) using test system of "Diaclone" (France) according to the manufacturer's instructions.Children with asthma have insufficient capacity of nonspecific protection that is determined by the severity of illness and is the most significant factor in patients with nonkontrol bronchial asthma (р
Keywords: bronchial asthma; children; immunity